Modeling and Comparing Brain Processes in Message and Earned Source Credibility Evaluation - Schneider, Piotr; Wójcik, Grzegorz M.; Kawiak, Andrzej; Kwasniewicz, Lukasz; Wierzbicki, Adam (Frontiers in Human Neuroscience, 2022)
Understanding how humans evaluate credibility is an important scientific question in the era of fake news. Source credibility is among the most important aspects of credibility evaluation. One of the most direct ways to understand source credibility is to use measurements of brain activity of humans who make credibility evaluations. This article reports the results of an experiment during which we have measured brain activity during credibility evaluation using EEG. In the experiment, participants had to learn source credibility of fictitious students based on a preparatory stage, during which they evaluated message credibility with perfect knowledge. The experiment allowed for identification of brain areas that were active when a participant made positive or negative source credibility evaluations. Based on experimental data, we modelled and predicted human source credibility evaluations using EEG brain activity measurements with F1 score exceeding 0.7 (using 10-fold cross-validation with 3 replications). We are also able to model and predict message credibility evaluations with perfect knowledge, and to compare both models obtained from a single experiment.